Acceleration of climate warming and plant dynamics in Antarctica - Cannone, Nicoletta; Malfasi, Francesco; Favero-Longo, Sergio Enrico; Convey, Peter; Guglielmin, Mauro (Current Biology, 2022)
: The strong air temperature warming between the 1950s and 2016 in the Antarctic Peninsula region1 exceeded the global average warming2,3 with evident impacts on terrestrial ecosystems and the two native Antarctic vascular plants Deschampsia antarctica Desv. and Colobanthus quitensis (Kunth) Bartl.4-10 Subsequently, a short but intense cooling occurred from the Antarctic Peninsula to the South Orkney Islands (1999-2016),1,11-13 impacting terrestrial ecosystems, with reduced lichen growth14 and no further expansion of D. antarctica in the Argentine Islands.5 The strong warming trend is predicted to resume15 with expansion of ice-free areas and continued impacts on the abiotic and biotic components of terrestrial ecosystems including the ingression of non-native species3,8,16,17 as recently recorded at Signy Island (South Orkney Islands).18-20 In this study we document acceleration in the expansion of D. antarctica and C. quitensis in the last decade (2009-2018) at Signy Island, where the air temperature warming trend resumed in summer after 2012. We hypothesize that the striking expansion of these plants is mainly triggered by summer air warming and release from the limitation of fur seal disturbance. We also hypothesize that the "pulse" climatic event of the strong air cooling detected in 2012 did not appear to influence the vegetation community dynamics on this island. This is the first evidence in Antarctica for accelerated ecosystem responses to climate warming, confirming similar observations in the Northern Hemisphere. Our findings support the hypothesis that future warming will trigger significant changes in these fragile Antarctic ecosystems.